Viral eradication is required for sustained improvement of patient‐reported outcomes in patients with hepatitis C. (15th July 2018) - Younossi, Zobair M.; Stepanova, Maria; Reddy, Rajender; Manns, Michael P.; Bourliere, Marc; Gordon, Stuart C.; Schiff, Eugene; Tran, Tram; Younossi, Issah; Racila, Andrei
Abstract: Background: Clearance of chronic HCV infection improves quality of life and other patient‐reported outcomes (PROs). Lack of placebo‐controlled data led to concerns about the extent of contribution of viral eradication to PRO improvement. Aim: To assess PRO changes in HCV patients initially randomized to placebo treatment who received SOF/VEL/VOX in a deferred treatment substudy. Methods: HCV‐infected direct‐acting antivirals‐experienced patients who received placebo treatment in POLARIS‐1 subsequently received SOF/VEL/VOX (400/100/100 mg) daily for 12 weeks. PROs were prospectively collected using SF‐36v2, CLDQ‐HCV, FACIT‐F, WPAI:SHP. Results: Of 147 patients treated, most were male (79%), white (82%), 33% had cirrhosis, 99% had HCV genotype 1 with SVR‐12 of 97%. During treatment with placebo, there were no significant changes in any PROs from patients' own baseline (all P  >   .05) except for the Worry domain of CLDQ‐HCV. However, soon after initiation of treatment with SOF/VEL/VOX, significant PRO improvements were noted: +2.4% to +8.1% of a PRO range size, P  <   .05 for 6 of the 26 studied PROs, by treatment week 4; +2.0% to +8.3%, P  <   .05 for 14/26 PROs by treatment week 12. Achieving SVR was associated with similar or greater PRO improvement: +2.5% to +11.9%, P  <   .05 for 24/26 PROs, by SVR‐12; +3.2% to +14.9%, P  <   .05 for 23/26 PROs, by SVR‐24. In multivariate regression analysis, being viraemic was associated with PRO impairment: beta from −2.4% to −8.5%, P  <   .05 for all but one PRO. Conclusion: Treatment with SOF/VEL/VOX for 12 weeks led to significant and sustainable improvement in patient‐reported outcomes in patients who had previously failed another direct‐acting antiviral regimen.